2014
DOI: 10.1016/j.dnarep.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

DNA Ligase IV regulates XRCC4 nuclear localization

Abstract: DNA Ligase IV, along with its interacting partner XRCC4, are essential for repairing DNA double strand breaks by non-homologous end joining (NHEJ). Together, they complete the final ligation step resolving the DNA break. Ligase IV is regulated by XRCC4 and XLF. However, the mechanism(s) by which Ligase IV control the NHEJ reaction and other NHEJ factor(s) remains poorly characterized. Here, we show that a C-terminal region of Ligase IV (aa 620 to 800), which encompasses a NLS, the BRCT I, and the XRCC4 interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…Nevertheless, the marked destabilization of Dnl4 protein caused by the single-site mutations indicated that they had a major impact on basal Dnl4–Lif1 interaction in the cell (Figure 3), consistent with the predictions of structural biology (Figure S5) [5, 6]. Such observations are also consistent with competitive displacement studies demonstrating that disruption of a single helix within the human LIG4 inter-BRCT linker was sufficient to destabilize the LIG4/XRCC4 interaction [22]. …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, the marked destabilization of Dnl4 protein caused by the single-site mutations indicated that they had a major impact on basal Dnl4–Lif1 interaction in the cell (Figure 3), consistent with the predictions of structural biology (Figure S5) [5, 6]. Such observations are also consistent with competitive displacement studies demonstrating that disruption of a single helix within the human LIG4 inter-BRCT linker was sufficient to destabilize the LIG4/XRCC4 interaction [22]. …”
Section: Discussionsupporting
confidence: 81%
“…In turn, evidence in humans suggests that binding of the LIG4 BRCT region might influence XRCC4–XLF multimerization, in part by preventing the XRCC4 C-terminus from interacting with the XRCC4–XLF interface [9, 12, 20, 21]. The human LIG4–XRCC4 interaction has also been shown to be required for proper nuclear localization and stability of XRCC4 [22]. …”
Section: Introductionmentioning
confidence: 99%
“…The nuclear localization of human XRCC4 is regulated by the XRCC4 NLS (amino acids 270-275), SUMO modification at K210 and regulation by DNA Ligase IV [5, 21, 33]. Yurchenko et al (2006) showed that SUMOylation at K210 is necessary and sufficient for the nuclear localization of XRCC4 [33].…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study, the chromatin binding of XRCC4 was absent in LIG4-disrupted cells derived from human pre-B leukemia cell Nalm-6 [13]. Additionally, Francis et al very recently demonstrated that XRCC4 existed in the cytoplasm and was absent in the nucleus in LIG4-disrupted Nalm-6 [14]. They also showed that XRCC4 in the nucleus was decreased in fibroblasts from two LIG4 syndrome patients (R278H and R814X, respectively) [14].…”
Section: Introductionmentioning
confidence: 88%
“…Additionally, Francis et al very recently demonstrated that XRCC4 existed in the cytoplasm and was absent in the nucleus in LIG4-disrupted Nalm-6 [14]. They also showed that XRCC4 in the nucleus was decreased in fibroblasts from two LIG4 syndrome patients (R278H and R814X, respectively) [14]. Girard et al identified two tandem NLS, i.e., KKRK and KMKK, which span amino acids 626-629 and 633-636, respectively [9].…”
Section: Introductionmentioning
confidence: 94%